Identification of a Novel Alternatively Spliced Form of Inflammatory Regulator SWAP-70-Like Adapter of T Cells - Marie Hashimoto; Jun-ichi Nagao; Shojiro Ikezaki; Sonoko Tasaki; Ken-ichi; Yuka Narita; Tamaki Cho; Kenji Yuasa; Amnon Altman; Yoshihiko Tanaka (Hindawi Limited, 2017)
Activation of naive CD4+ T cells results in the development of several distinct subsets of effector Th cells, including Th2 cells that play a pivotal role in allergic inflammation and helminthic infections. SWAP-70-like adapter of T cells (SLAT), also known as Def6 or IBP, is a guanine nucleotide exchange factor for small GTPases, which regulates CD4+ T cell inflammatory responses by controlling Ca2+/NFAT signaling. In this study, we have identified a novel alternatively spliced isoform of SLAT, named SLAT2, which lacks the region encoded by exons 2-7 of the Def6 gene. SLAT2 was selectively expressed in differentiated Th2 cells after the second round of in vitro stimulation, but not in differentiated Th1, Th17, or regulatory T (Treg) cells. Functional assays revealed that SLAT2 shared with SLAT the ability to enhance T cell receptor- (TCR-) mediated activation of NFAT and production of IL-4 but was unable to enhance TCR-induced adhesion to ICAM-1. Ectopic expression of SLAT2 or SLAT in Jurkat T cells resulted in the expression of distinct forms of filopodia, namely, short versus long ones, respectively. These results demonstrate that modulating either SLAT2 or SLAT protein expression could play critical roles in cytokine production and actin reorganization during inflammatory immune responses.